Description of Snakebite's Prevention Efforts Towards Farmers in Panti Sub-District - Rismawan Adi Yunanto; Wantiyah Wantiyah; Yusuf Gito Afandi (KHD-Production, 2021)
The knowledge toward snakebite prevention was related to preventive measures taken by farmers. Besides, a lack of farmer’s awareness about the importance of using personal protective equipment and a lack of public understanding regarding the level of danger and the types of venomous snakes were factors that cause snakebites. This study aimed to describe the efforts to prevent snakebite on farmers in Panti sub-district. The method used a quantitative descriptive with survey research design. This research was conducted on farmers in Panti with a sample of 100 respondents using cluster sampling technique. The results of this study showed respondents have known tree crevices, earthen holes, piles of wood, garbage, and twigs that are at risk of becoming snake habitats, use boots and trousers while working, maximize lighting using a lamp or flashlight, regularly mow grass and shrubs, clean up scattered leaves, and rest on higher ground when at home or in the fields. While only a few respondents participated in health education and counselling regarding snake bites. This study concluded that the majority of respondents conducted efforts to prevent snakebites.